A comparison of arterial stiffness in hypertensive patients with controlled and uncontrolled systolic blood pressure using pulse wave velocity measurement - Reena Sharma, Fokeer (2011)
Arterial stiffness is an important predictor of increased cardiovascular events. It has been shown to be strongly positively correlated with systolic blood pressure. The pulse wave velocity (PWV) is a non invasive measure of arterial stiffness and can reliably predict the degree of arterial stiffness in hypertensive patients who are asymptomatic of cardiovascular disease but who are at risk of developing ischemic heart disease. In hypertensive patients, uncontrolled systolic blood pressure is associated with a higher pulse wave velocity, which corresponds to a greater degree of arterial stiffness compared to hypertensive subjects with well controlled systolic blood pressure. Therefore those patients with uncontrolled systolic blood pressure and increased arterial stiffuess are at higher risk of developing cardiovascular events. The objective of this study was to determine a difference in the pulse wave velocity (PWV) between controlled and uncontrolled systolic blood pressure (SBP) in hypertensive subjects at Hospital Universiti Sains Malaysia (HUSM). This is a cross sectional study. 84 hypertensive patients were recruited. They were equally divided into 2 groups (controlled and uncontrolled systolic blood pressure) based upon the systolic blood pressure readings observed over the previous 6 months. The pulse wave velocity was determined using standard methods, using the Sphygmocor ® machine, which is an automated tonometer. The right carotid and right femoral pulse waves were the sites used in this study to determine the pulse wave velocity.(W-C Yu eta/., 2008) There was no significant difference in the baseline characteristics between the two groups, except for the systolic blood pressure. It was observed that there was a statistically significant difference in the PWV in the uncontrolled SBP group (12.9 m/s) compared to the PWV in the controlled SBP group((9.9m/s, p<O.OOl). This study has shown that pulse wave velocity is higher in hypertensive patients with an uncontrolled systolic blood pressure. Hence pulse wave velocity may be considered to be a useful non invasive tool for early screening of cardiovascular disease in hypertensive patients, since arterial stiffness is a proven surrogate marker for future cardiovascular events.